2021
DOI: 10.1039/d1tc01001h
|View full text |Cite
|
Sign up to set email alerts
|

Achieving 46% efficient white-light emissive carbon dot-based materials by enhancing phosphorescence for single-component white-light-emitting diodes

Abstract: White-light-emitting carbon dots (CDs) with fluorescence/phosphorescence dual-emission feature is great importance for single-phase white-light-emitting diodes (WLEDs), but so far rather limited due to weak phosphorescence. Herein, a highly efficient white-light...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 44 publications
1
41
0
Order By: Relevance
“…Structure and Phosphorescence . At present, transition metal-based complexes, rare earth-based phosphors, and pure organic compounds are mainly the traditional phosphorescent materials. However, these phosphorescent materials have the following shortcomings: high cost and complex preparation and purification processes; strict conditions are required to effectively produce phosphorescence. , Some exciting progress has been made in the field of long lifetime RTP CDs, which enables CDs suitable for various important applications. However, there are still relatively few studies on the phosphorescence mechanism of CDs. In this section, we summarize the progress of CDs in the field of phosphorescence in recent years and the unique role of theoretical calculations in revealing the mechanism of phosphorescence.…”
mentioning
confidence: 99%
“…Structure and Phosphorescence . At present, transition metal-based complexes, rare earth-based phosphors, and pure organic compounds are mainly the traditional phosphorescent materials. However, these phosphorescent materials have the following shortcomings: high cost and complex preparation and purification processes; strict conditions are required to effectively produce phosphorescence. , Some exciting progress has been made in the field of long lifetime RTP CDs, which enables CDs suitable for various important applications. However, there are still relatively few studies on the phosphorescence mechanism of CDs. In this section, we summarize the progress of CDs in the field of phosphorescence in recent years and the unique role of theoretical calculations in revealing the mechanism of phosphorescence.…”
mentioning
confidence: 99%
“…4(a)) shows a typical absorption peak at 237 nm corresponding to the π–π* transition. 52 We also studied the optical properties of the CDs. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Fourier transform infrared (FTIR) spectra (Figure 2B) reveal that the CDs exhibit characteristic absorption peaks at 3400, 1631, and 1617 cm −1 , assigned to the O─H, C═O, and C═C stretching vibrations, respectively 27 . After incorporating the CDs into the thermal annealed BA matrix, new absorption peaks can be observed at 941 cm −1 , corresponding to the C─B stretching vibration, 18,21,22 indicating BA molecules functionalized on the CDs after thermal treatment. In the XPS results, the high‐resolution B 1 s spectrum of t‐CD@BA (Figure 2C) displays three bands centered at 194.6, 193.6, and 192.7 eV, assigned to B─O, B 2 O 3 , and BCO 2 , respectively, 18 implying dehydration process occurs among CDs and BA molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Carbon dots (CDs) are emerging as a new class of phosphorescence nanomaterials, 11–17 which have attracted significant attention because of their attractive properties, such as simple synthetic routes, low cost, and high photostability. Recently, a principle on manipulating intersystem crossing (ISC) by incorporating heteroatoms into CDs (e.g., N, P, B, and halogens) was proposed to achieve effective RTP 18–23 . Liu et al obtained N,P‐doped CDs with a PQY of 17.5%, 18 while Wang et al reported B,P‐doped CDs that exhibited a high PQY of 23% 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation